Digitonin-facilitated delivery of imaging probes enables single-cell analysis of AKT signalling activities in suspension cells. Issue 17 (5th August 2021) - Wang, Siwen; Perkins, Nicole G.; Ji, Fei; Chaudhuri, Rohit; Guo, Zhili; Sarkar, Priyanka; Shao, Shiqun; Li, Zhonghan; Xue, Min
Abstract : Digitonin allows the delivery of cyclic peptide-based imaging probes into suspension cells. This method enables time-resolved single-cell profiling of AKT signalling activities. Abstract : Analyzing intracellular signalling protein activities in living cells promises a better understanding of the signalling cascade and related biological processes. We have previously developed cyclic peptide-based probes for analyzing intracellular AKT signalling activities, but these peptide probes were not cell-permeable. Implementing fusogenic liposomes as delivery vehicles could circumvent the problem when analyzing adherent cells, but it remained challenging to study suspension cells using similar approaches. Here, we present a method for delivering these imaging probes into suspension cells using digitonin, which could transiently perforate the cell membrane. Using U87, THP-1, and Jurkat cells as model systems representing suspended adherent cells, myeloid cells, and lymphoid cells, we demonstrated that low concentrations of digitonin enabled a sufficient amount of probes to enter the cytosol without affecting cell viability. We further combined this delivery method with a microwell single-cell chip and interrogated the AKT signalling dynamics in THP-1 and Jurkat cells, followed by immunofluorescence-based quantitation of AKT expression levels. We resolved the cellular heterogeneity in AKT signalling activities and showed that the kinetic patterns of AKT signalling and the AKT expression levels were related in THP-1 cells, but decoupled in Jurkat cells. We expect that our approach can be adapted to study other suspension cells.